Cross-border Planning in Europe – The Case of ULYSSES - Jung, Wolfgang; Brester, Benedikt; Putlitz, Andreas; Kaisto, Virpi; Sylaios, Georgios; Feliu, Efren; Tapia, Carlos; Chilla, Tobias; Wolf, Jan-Hendrik; Castro, Eduardo Anselmo (AESOP, 2012)
ULYSSES is a case study-oriented project focusing on the implementation of applied research results produced under the ESPON 2006 and ESPON 2013 Programmes as a reference framework for decentralised cross-border spatial development planning. The project aims to generate analytical results rather than harmonising quantitative data across borders. ULYSSES covers six cross-border regions: the Upper Rhine area (France, Germany, Switzerland); the Spanish-French land border (Pyrenees); the Greece–Bulgaria border; the Northern Finland–Russia border (Karelia); the Poland–Germany–Sweden border (land and maritime); and the Spain–Portugal border (Extremadura/Alentejo). Three of these are highlighted as case studies: Karelia (a Northern European border with an EU external frontier), Greece–Bulgaria (a Southern European border involving a new EU member state), and the Upper Rhine (a central European “old” border area). The paper provides an overview of each area, presents the results of a factor analysis, and summarises the lessons learned. Using a multi-scale performance analysis and cross-border institutional assessment, the Transnational Partnership Group of ULYSSES explored how borders affect economic performance and social interaction. The findings show to what extent border regions, often located on the periphery of their countries, are shaped by their cross-border conditions.
Book of proceedings : AESOP 26th Annual Congress 11-15 July 2012 METU, Ankara
Keywords: Cross-border planning; ESPON; Institutional analysis; Border regions; European spatial development